PENGEMBANGAN PROTOTIPE ALAT KEAMANAN BARANG ELEKTRONIK BERBASIS INTERNET OF THINGS (IOT) - Nur Athif Oldika Gunawan; Nila Feby Puspitasari; Bambang Pilu Hartato (JURNAL ELEKTROSISTA, 2024)
The increasing security risks today have driven the development of more sophisticated protection solutions, especially for personal electronic goods. This study aims to design and implement an innovative Internet of Things (IoT)-based security device, designed to protect electronic goods such as mobile phones, laptops, and other electronic devices. The technology used includes the integration of smart sensors, such as GPS, Ultrasonic, and Passive Infrared, which function to detect threats accurately and responsively. This prototype-based system is equipped with smart sensors designed to detect potential threats to personal goods. In addition, a user application was successfully developed to support efficient interaction between users and the system. The test results show that this system is portable and capable of providing real-time notifications to users regarding threats to electronic goods, as well as responding to these threats quickly and appropriately. The approach taken not only emphasizes physical security, but also integrates modern technology to provide an efficient, practical, and easily accessible monitoring experience. This study offers an innovative solution in protecting personal electronic goods in the digital era.